Pemanfaatan Limbah Kopi menjadi Briket Arang sebagai Bahan Bakar Alternatif - Hendrawan Hendrawan; Ramdani Ramdani; Puji Rahayu Rahayu; Alviani Halimatus Sadiah Sadiah (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
Indonesia is one of the world’s largest coffee producers, with the village of Campakamulya being a producer of Puntang coffee. Increased coffee production generates coffee husk and grounds waste that has not been utilised optimally, thus posing a potential risk of environmental pollution. This community service initiative aims to process coffee waste into briquettes as an environmentally friendly alternative energy source. The partners in this initiative are the local community and small and medium-sized enterprises (SMEs). The method employed was Participatory Action Research (PAR), involving the community in the stages of observation, planning, implementation, and evaluation. The results of the activity demonstrated that the community was able to produce briquettes through the stages of sun-drying, roasting, grinding, mixing, moulding, and drying. The resulting product not only serves as an alternative energy source but also creates business opportunities and enhances the community’s skills. This activity demonstrates that the utilisation of coffee waste holds potential as a sustainable solution for waste management and community economic development.